Sistem Informasi Persediaan Barang Berbasis Web Di Toko Jam Sumber Terang Jember - Titasari Rahmawati; Hermawan Andika (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
The rapid development of technology makes the business world more efficient and effective, so information becomes crucial for business success. The implementation of information presentation for business purposes has been widely realized in the form of information systems that are indispensable for managing and understanding business processes, especially in complex environments such as the Clock Shop Sumber Terang Jember, where employees are assigned to check goods manually with paper media, but the ability to data is not on time. This method also causes problems such as delayed data transmission and delays in handling the recording of large quantities of goods. Another problem that arises is that the data search process will take a long time. To answer these challenges, a website system will be developed to provide comprehensive information about warehouse inventory. This system is designed to overcome the problem of delay and inefficiency caused by manual recording. This information system uses HTML, PHP, Bootstrap CSS Framework, and MySQL technologies. The main features provided include login, management of item data, item categories, users, checklists, approval of item checking data, and report generation. System implementation includes hardware and software specifications, as well as a user interface designed to simplify the inventory management process. The conclusion of this research shows that the information system developed can help check goods more quickly and efficiently. Suggestions for further development include the addition of goods inspection features and stock management.